Mapping of graphic-semantic representations in design teaching - Rijo, Cátia (2022)
This article proposes a reflection on the visual thinking tools used in graphic design teaching as an active methodology that help the synthesis process of the expressive code and support graphic expression and semantics in design practice. It’s intended to analyze more specifically the use of mood boards as an imagery tool in the creation of a brand mark and its relationship with expressive codes. To build a relevant and meaningful brand mark, it is important to be aware of the semantic elements used. Tools like mood boards help students with the aesthetic-symbolic references of the form and make the semantic concepts more perceptible. At the end we analyze mood boards and their relationship with semantics in the creation of brand marks. © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.